Genetics, genomics, and diet interactions in obesity in the Latin American environment - Patricia Guevara-Ramírez; Santiago Cadena-Ullauri; Viviana A. Ruiz-Pozo; Rafael Tamayo-Trujillo; Elius Paz-Cruz; Daniel Simancas-Racines; Ana Karina Zambrano (Frontiers in Nutrition, 2022)
Obesity is a chronic disease characterized by abnormal or excessive fat accumulation that could impact an individual’s health; moreover, the World Health Organization (WHO) has declared obesity a global epidemic since 1997. In Latin America, in 2016, reports indicated that 24.2% of the adult population was obese. The environmental factor or specific behaviors like dietary intake or physical activity have a vital role in the development of a condition like obesity, but the interaction of genes could contribute to that predisposition. Hence, it is vital to understand the relationship between genes and disease. Indeed, genetics in nutrition studies the genetic variations and their effect on dietary response; while genomics in nutrition studies the role of nutrients in gene expression. The present review represents a compendium of the dietary behaviors in the Latin American environment and the interactions of genes with their single nucleotide polymorphisms (SNPs) associated with obesity, including the risk allele frequencies in the Latin American population. Additionally, a bibliographical selection of several studies has been included; these studies examined the impact that dietary patterns in Latin American environments have on the expression of numerous genes involved in obesity-associated metabolic pathways.